The Effect of Early Mobilization on Pain Intensity in Post-Cesarean Section (CS) Patients in Ward 2B at Grandmed Hospital Lubuk Pakam - Anita Sri Gandaria Purba; Pitirani; Dian Anggri Yanti; Nadya Ulfa Kesumawardani; Yuliasri Saragih (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2026)
Cesarean section is a commonly performed delivery procedure that may cause postoperative pain due to tissue incision. Inadequately managed pain can delay the patient’s recovery process. One of the non-pharmacological interventions that can be applied to reduce pain is early mobilization. This study aimed to determine the effect of early mobilization on pain intensity among post-cesarean section patients in Ward 2B at Grandmed Hospital Lubuk Pakam in 2025. This study employed a quantitative approach using a quasi-experimental design with a one-group pretest-posttest design. The sample consisted of 30 respondents selected using purposive sampling technique. Pain intensity was measured using the Numeric Rating Scale (NRS) before and after the early mobilization intervention. Data were analyzed using a paired t-test with a significance level of 0.05. The results showed that before the intervention, the majority of respondents experienced severe pain (66.7%), whereas after early mobilization, most respondents experienced a decrease to mild pain (76.7%). The mean pain intensity decreased from 0.6667 to 0.2333 after the intervention. Statistical analysis revealed a p-value of 0.000 (p < 0.05), indicating a significant effect of early mobilization on reducing pain intensity. In conclusion, early mobilization is effective in reducing pain intensity in post-cesarean section patients and can be recommended as a non-pharmacological intervention in postoperative care.